2014
DOI: 10.3340/jkns.2014.56.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Clinical and Radiological Outcomes of a Zero-Profile Device Concerning Reduced Postoperative Dysphagia after Single Level Anterior Cervical Discectomy and Fusion

Abstract: ObjectiveThis study analyzed clinical and radiological outcomes of a zero-profile anchored spacer (Zero-P) and conventional cage-plate (CCP) for single level anterior cervical discectomy and fusion (ACDF) to compare the incidence and difference of postoperative dysphagia with both devices.MethodsWe retrospectively reviewed our experiences of single level ACDF with the CCP and Zero-P. From January 2011 to December 2013, 48 patients who had single level herniated intervertebral disc were operated on using ACDF, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 18 publications
0
33
0
Order By: Relevance
“…Although the pathogenesis of the dysphagia is yet to be precisely known, it has been reported that the zero-profile designed stand-alone cage may effectively reduce the incidence of long-term dysphagia without irritation of implants which were directly placed posterior to the esophagus [2,24]. In addition, some authors suggest that post-operative dysphagia may be caused by direct trauma to the esophagus and its surrounding tissue during the surgery [2,25]. The selflocking stand-alone cage can make the operative procedure simpler with less retraction of the esophageal.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although the pathogenesis of the dysphagia is yet to be precisely known, it has been reported that the zero-profile designed stand-alone cage may effectively reduce the incidence of long-term dysphagia without irritation of implants which were directly placed posterior to the esophagus [2,24]. In addition, some authors suggest that post-operative dysphagia may be caused by direct trauma to the esophagus and its surrounding tissue during the surgery [2,25]. The selflocking stand-alone cage can make the operative procedure simpler with less retraction of the esophageal.…”
Section: Discussionmentioning
confidence: 98%
“…Dysphagia is common after anterior cervical spine surgery especially in the multi-level ACDF [11,24,25]. Although the pathogenesis of the dysphagia is yet to be precisely known, it has been reported that the zero-profile designed stand-alone cage may effectively reduce the incidence of long-term dysphagia without irritation of implants which were directly placed posterior to the esophagus [2,24].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown equivalent radiographic and clinical results as well as a lower incidence of postoperative dysphagia. 24 - 30 However, no study has directly compared the 2 groups with regard to length of stay, ambulatory versus inpatient status, and overall complication profiles, leading many skeptics to question the safety of stand-alone cages.…”
Section: Discussionmentioning
confidence: 99%
“…The authors observed that, at the final follow-up, dysphagia rate was significantly lower in the group of PEEK-titanium combined anchored cage (0.4%, 1 of 266) as compared to the group of anterior cervical cage-plate (6.7%, 20 of 300) (p=0.01)14). Similarly, Son et al23) also reported that the dysphagia rate 6 months after ACDF using anterior cervical plate was 22.2% as compared with PEEK-titanium combined anchored cage (0%) (p=0.02).…”
Section: Discussionmentioning
confidence: 81%